The Influence of Organizational Culture and Motivation on Employee Performance at PT. Malindo Feedmill Tbk - Andani, Yospila; Santoso, Arief Budi (Implikasi: Jurnal Manajemen Sumber Daya Manusia, 2024)
The purpose of this study was to determine how much influence organizational culture and motivation have on employee performance at PT. Malindo Feedmill Tbk. The method in this study used a quantitative method with a saturated sampling technique totaling 70 respondents. Data analysis techniques used data instrument tests, classical assumption tests, simple linear regression, multiple linear regression, coefficient of determination. Hypothesis testing in this study used the t test and F test. Based on the results of the study, organizational culture has a significant effect on employee performance with a coefficient of determination of 0.348, meaning that employee performance is influenced by organizational culture and motivation by 34.8% and the remaining 65.2% is influenced by other factors. This has been proven by the organizational culture variable, the t test obtained a calculated t value> t table or (4.167> 1.667). In the motivation variable, the t test results obtained (2.742> 1.667). Organizational Culture and Motivation Giving simultaneously have a positive effect on employee performance, which has been shown in the multiple linear regression equation Y = 8.835 + 0.321 X1 + 0.175 X2. Hypothesis testing obtained the value of F count > F table or (17.848 > 3.134) this is also strengthened by the p value < Sign. 0.05 or (0.000 < 0.05). Thus, H03 is accepted, this shows that there is a significant influence simultaneously between organizational culture and motivation giving on employee performance.